Mandibular advancement splints for the treatment of sleep apnoea syndrome (Swiss Medical Weekly, 2011)
Oral devices, in particular Mandibular Advancement Splints (MAS), which hold the mandible in a protruded position during sleep, are increasingly used for the treatment of Obstructive Sleep Apnoea (OSA). These devices can be effective in treating OSA across a range of severity. Complete resolution of OSA (Apnoea-Hypopnoea Index [AHI] reduced